THE INFLUENCE OF DIGITAL MEDIA ON READING AND WRITING PRACTICES - Oybek Temirxo'jayev Dilshodjon O'g'li, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the profound impact of digital media on contemporary reading and writing practices. It explores how the proliferation of online platforms and digital devices has fostered new modes of literacy, including hypertext, multimedia storytelling, and collaborative writing. By analyzing the advantages and disadvantages of these emerging practices, the article highlights the challenges and opportunities presented by the digital landscape for both reading and writing. It concludes by discussing the need for educators and researchers to navigate the complexities of this evolving media environment and foster critical digital literacy skills in individuals.